Penyuluhan Ispa Pada Anak Di Sdn 03 Desa Suka Maju Kabupaten Mukomuko - Martiningsih; Widiana , Ari; Yunita , Andri; Indhika, Vera; Nurkhasanah, Ria Devita (Utami Publisher, 2025)
ARI (acute respiratory tract infection) is an acute infectious disease that attacks one or more respiratory organs that can last for 2 weeks. Acute respiratory tract infection (ARI) is caused by bacteria and viruses. ARI disease is often suffered by children is also the main killer. This counseling activity aims to help reduce the transmission of ARI and increase knowledge about ARI in children in SDN 03 Desa Suka Maju. ARI is a disease that is always ranked 10 most diseases based on the number of visits at the Penarik Puskesmas Mukomuko Regency. The method used in counseling is the translation of ARI such as risk factors, complications, sneezing ethics and coughing, and when to go to health facilities. In addition to the description there are also quizs with prizes and the distribution of masks to students. Thus it is expected that the knowledge of students and teachers about ARI will be even greater so that it will be able to reduce the level of transmission of ARI. The benchmark for the success of this extension is the pre and post test results which increased before and after the extension, and children are able to practice sneezing and coughing etiquette.